“A Piece of Sanity in the Midst of Insane Times”: Girls on the Run Programming to Promote Physical Activity and Psychosocial Well-Being During the COVID-19 Pandemic - Weiss, Maureen R.; Kipp, Lindsay E.; Riley, Allison (Frontiers in Public Health, 2021)
Afterschool programs have the potential to promote social, emotional, and physical health outcomes among youth participants. The positive youth development (PYD) framework argues that acquiring desirable attitudes and behaviors occurs when skill-building opportunities are explicitly provided within a safe and supportive climate guided by caring, competent, and compassionate instructors. Girls on the Run (GOTR) is a PYD program that uses running, motor skills, and physical activities as a platform for promoting positive psychosocial outcomes and life skills learning among elementary- and middle school-aged girls. The onset of the COVID-19 pandemic challenged GOTR to modify lessons, coach training, and program delivery (fully in-person, fully virtual, or hybrid) to accommodate public health guidelines. Following the Fall 2020 season, parents (n = 1617) and coaches (n = 991) representing 1077 teams of 39 councils completed an online survey about program experiences due to COVID-19 restrictions. Both parents and coaches positively rated program impact regardless of delivery mode, although in-person mode was rated higher for satisfaction with the end-of-season event. Thematic analysis of open-ended responses revealed that parents and coaches identified increased physical activity opportunities and life skills learning as well as improved social, psychological, and emotional development as a result of participating. Both stakeholders noted GOTR provided “a sense of normalcy” during this time of great need. Findings provide information for PA-PYD programs to make improvements for implementation during challenging times.